Location of Production Facilities in the Framework of Sustainable Development. (2016) - Burciu, Stefan; Popa, Mihaela; Rosca, Eugen; Rusca, Florin; Costescu, Dorinela
Abstract: Sustainable development is a necessity, solutions for satisfying users' needs having to be adopted in relation to criteria that often integrate divergent interests of those involved. The optimal location of production centers has the best effect on production costs. The paper focuses on industrial location from the user's point of view, taking into account elements like maximum distance for efficient road transportation, resources proximity and available infrastructure. The developed model has a large scale of applicability in economic sectors like: distribution, automotive industry, constructions. Results of applying this model proved its utility and necessity of further researches on location problems.